Differences in agency? How adolescents from 18 countries perceive and cope with their futures - Seiffge-Krenke, Inge; Persike, Malte; Chau, Cecilia; Hendry, Leo B.; Kloepp, Marion; Terzini-Hollar, Michelle; Tam, Vicky; Rodríguez Naranjo, Carmen; Herrera, Dora; Menna, Palma; Rohail, Iffat; Veisson, Marika; et al. (International Journal of Behavioral Development, 2012)
This study investigated how N = 5,126 adolescents (mean age of 15 years) from 18 countries perceive and cope with future- and school-related stress. The adolescents completed the Problem Questionnaire (PQ), which assesses stress, and the Coping Across Situations Questionnaire (CASQ), which assesses three coping styles (reflection/support-seeking, emotional outlet, and withdrawal/denial). Across countries, adolescents reported considerably higher levels of future-related stress than school-related stress. The adolescents actively coped with stressors in both domains and seldom relied on emotional outlet or withdrawal/denial. A clustering of the countries according to socioeconomic criteria and geographical proximity demonstrated that adolescents from the continental group of countries showed low stress and high coping. Adolescents in the east/Asia group showed medium stress and low coping and those in the south group showed high stress and low coping. Developmental context was more strongly associated with stress perception and coping, style than age or gender, a finding relevant for prevention approaches aiming to endorse positive orientation to the future and improve coping competence.
Keywords: academic stress; coping; cross-cultural study; fearful future anticipations